Metal–semiconductor–metal ternary heteronanocrystals with multiple plasmonic effects for efficient photocatalysis. Issue 3 (3rd January 2023) - Wi, Dae Han; Yang, Hyunwoo; Kim, Yonghyeon; Ahn, Hojin; Hong, Jong Wook; Han, Sang Woo
Abstract : A synthetic strategy for the controlled construction of plasmonic metal–semiconductor–plasmonic metal ternary heteronanocrystals with multiple plasmonic effects was developed. Abstract : Regarding the design of high-performance solar energy conversion platforms, heteronanostructured photocatalysts consisting of plasmonic metals and semiconductors are of particular interest due to their capability for the conversion of solar to plasmon energy that can accelerate the formation of charge carriers. Here, we introduce ternary heteronanocrystals composed of two different plasmonic metal nanocrystals (hexoctahedral Au and spherical Ag nanocrystals) and a semiconductor (Cu2 O). The site-selective overgrowth of Cu2 O on the high-curvature vertices of hexoctahedral Au nanocrystals and the subsequent deposition of spherical Ag nanocrystals on the Cu2 O surface could realize the formation of Au–Cu2 O–Ag ternary heteronanocrystals with a precisely controlled configuration. The synthesized ternary heteronanocrystals exhibited enhanced photocatalytic H2 evolution performance over a wide range of visible-light wavelengths compared to binary and monomeric counterparts. The improved photocatalytic function of the ternary heteronanocrystals can be attributed to the combination of the two different plasmonic metal nanocrystals having distinct plasmonic properties with the semiconductor, which can enable the promotion of both plasmon-induced charge and energy transfer processes. Our study can give a design guideline for devising heteronanostructure-based solar energy conversion platforms with intended functions.